Serial Entrepreneurship: Learning by Doing? - Lafontaine, Francine; Shaw, Kathryn (Journal of Labor Economics, 2016)
Among typical entrepreneurs, is serial entrepreneurship common? Is the serial entrepreneur more likely to succeed? If so, why? These questions are addressed using data on all establishments started between 1990 and 2011 to sell retail goods and services in Texas. An entrepreneur is the owner of a new business. A serial entrepreneur is one who opens repeat businesses. We find that 25.6% of businesses are operated by serial entrepreneurs. These are the more successful businesses: prior business experience increases the longevity of the next business opened. Results with owner fixed effects suggest that past experience imparts valuable business skills.